Handbook of ethological methods - Lehner, Philip N., 1940-; Cambridge University Press (Cambridge : Cambridge University, 1996)
"At first glance, studying behavior is easy, but as every budding ethologist quickly realises, there are a host of complex practical, methodological and analytical problems to solve before designing and conducting the study. How do you choose which species or which behavior to study? What equipment will you need to observe and record behavior successfully? How do you record data in the dark, in the wet or without missing part of the action? How do you analyse and interpret the data to yield meaningful information?" "This new expanded edition of the Handbook of ethological methods provides a complete, step-by-step introduction to ethological methods from topic choice and behavioral description to data collection and statistical analysis. This book will be a must for beginning students and experienced researchers studying animal behavior in the field or laboratory."--BOOK JACKET
A conceptual model of animal behavior -- Choice of subjects -- Reconnaissance observation -- Delineation of research -- Design of research -- Experimental research -- Data collection methods -- Data-collection equipment -- Selected examples od data collection and description -- Introduction to statistical analysis -- Selection of a statistical test -- Parametric statistical tests -- Nonparametric statistical tests -- Rates of behavior and analysis of sequences -- Multivariate analyses -- Spatial orientation and time : circular statistics and spatial patterns -- Interpretation and presentation of results
Includes bibliographical references (pages [617]-663) and index
Keywords: Animal behavior -- Methodology -- Handbooks, manuals, etc